Architecture as the Inversion of Architecture - James Wines (Oz, 1987)
De-architecture is a frame of reference for questioning the nature and practice of architecture in the late 1980s and beyond. The term was invented because, as Picasso once observed, "Art is a series of destructions,'' and the concept of subtracting from an institutional definition to re-evaluate its purposes seemed an appropriate way to proceed.